2020
DOI: 10.1371/journal.pone.0232191
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective cohort study evaluating correlates of deep tissue infections among patients enrolled in opioid agonist treatment using administrative data in Ontario, Canada

Abstract: The objective of this study was to evaluate the relationship between individual characteristics and deep tissue infections in patients enrolled in opioid agonist treatment in Ontario, Canada. Methods A retrospective cohort study was conducted on patients in opioid agonist treatment between January 1, 2011, and December 31, 2015 in Ontario, Canada. Patients were identified using data from the Ontario Health Insurance Plan Database, and the Ontario Drug Benefit Plan Database. We identified other study variables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 77 publications
3
19
0
Order By: Relevance
“…Similar to findings in other studies, we found that OAT alone was associated with positive outcomes for patients with OUD [ 64 67 ]. In this study, we grouped patients based on their access to physician-based mental health services during their first year of OAT.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar to findings in other studies, we found that OAT alone was associated with positive outcomes for patients with OUD [ 64 67 ]. In this study, we grouped patients based on their access to physician-based mental health services during their first year of OAT.…”
Section: Discussionsupporting
confidence: 91%
“…Although OAT has been shown to be very effective, its efficacy may be negatively impacted by concurrent issues, including mental disorders [ 11 , 12 ], psychosocial problems [ 10 12 , 17 , 27 ] and infections such as HIV and viral Hepatitis [ 28 32 ]. The prevalence of comorbidities present major public health concerns in terms of the risk of complications from chronic physical health issues as well as poorer health system and treatment outcomes [ 11 , 17 , 33 , 34 ]. As the severity of the opioid issue continues to rise, the expansion and integration of OAT with other health services—more specifically, primary care and mental health services—has been recommended as a strategy to mitigate the opioid crisis [ 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to findings in other studies, we found that OAT alone was associated with positive outcomes for patients with OUD [64][65][66][67]. In this study, we grouped patients based on their access to physician-based mental health services during their first year of OAT.…”
Section: Discussionsupporting
confidence: 76%
“…Although OAT has been shown to be very effective, its efficacy may be negatively impacted by concurrent issues, including mental disorders [11,12], psychosocial problems [10-12, 17, 27] and infections such as HIV and viral Hepatitis [28][29][30][31][32]. The prevalence of comorbidities present major public health concerns in terms of the risk of complications from chronic physical health issues as well as poorer health system and treatment outcomes [11,17,33,34]. As the severity of the opioid issue continues to rise, the expansion and integration of OAT with other health services-more specifically, primary care and mental health services-has been recommended as a strategy to mitigate the opioid crisis [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…Four geographical groups were created (Northern/Rural, Northern/Urban, Southern/Rural, Southern/Urban). Comorbidity were all extracted from the OHIP database and HIV status (positive vs negative), defined by a validated ICES algorithm [ 17 ]; deep tissue infections including endocarditis (OHIP fee code 429), osteomyelitis (OHIP fee code 730) and septic arthritis (OHIP fee code 711), which have been defined in previously published research [ 18 ] and all found to be associated with injection drug use; mental health disorders (yes vs no), listed in Appendix B (Table 6 ). Health care use variables were counted after the patient started in OAT and included: number of emergency department visits (ED), identified using the Canadian Institute for Health Information National Ambulatory Care Reporting System (NACRS), the number of hospital admissions, identified using the Canadian Institute for Health Information Discharge Abstract Database (DAD) and primary care visits (median), identified using the Ontario Health Insurance Plan database (OHIP).…”
Section: Methodsmentioning
confidence: 99%